PENGARUH FASILITAS BELAJAR TERHADAP MOTIVASI BELAJAR SISWA DI SMP NEGERI 3 ANGGREK KABUPATEN GORONTALO UTARA - Nelviana Djambar; Meyko Panigoro; Fatmawaty Damiti; Roy Hasiru; Rierind Koniyo (Jurnal Pendidikan Ekonomi (JURKAMI), 2026)
This study aims to determine the effect of learning facilities on students’ learning motivation at SMP Negeri 3 Anggrek, North Gorontalo Regency. The study employed a quantitative approach with a correlational research design. The population of this study consisted of all students of SMP Negeri 3 Anggrek, with a sample of 56 students selected using a specific sampling technique. Data were collected through the distribution of questionnaires that had been tested for validity and reliability to ensure the accuracy of the research instruments. The collected data were then analyzed using simple linear regression analysis to examine the magnitude of the influence of learning facilities on students’ learning motivation. The results of the data analysis indicate that learning facilities have a significant effect on students’ learning motivation, with a contribution value of 20.8%. This finding suggests that better learning facilities are associated with higher levels of students’ learning motivation. However, 79.2% of students’ learning motivation is influenced by other factors beyond the variables examined in this study, such as the family environment, teaching methods, the role of teachers, and students’ internal factors. Therefore, it can be concluded that learning facilities are an important factor in enhancing students’ learning motivation; however, they need to be supported by other contributing factors to optimize students’ overall learning motivation.